solve y=3x + 5 Equation 1: 3x+y=53x+y=5 Equation 2: 5x-4y=-35x−4y=−3 These equations for that que

Question

solve

y=3x + 5

Equation 1: 3x+y=53x+y=5

Equation 2: 5x-4y=-35x−4y=−3 These equations for that question down below

Now that we’ve solved for y in Equation 1, it’s time to substitute the resulting expression into Equation 2.

What will Equation 2 look like when we substitute correctly.

in progress 0
Eloise 2 weeks 2021-10-14T01:10:26+00:00 1 Answer 0

Answers ( )

    0
    2021-10-14T01:11:35+00:00

    Answer:

    x=1, y=2. (1, 2).

    Step-by-step explanation:

    3x+y=5

    5x-4y=-3

    ————–

    y=5-3x

    5x-4(5-3x)=-3

    5x-20+12x=-3

    17x-20=-3

    17x=-3+20

    17x=17

    x=17/17=1

    y=5-3(1)=5-3=2

    x=1, y=2.

Leave an answer

Browse
Browse

27:3+15-4x7+3-1=? ( )